Cumulative probability of false-positive recall or biopsy recommendation after 10 years of screening mammography: a cohort study - Hubbard, Rebecca A; Kerlikowske, Karla; Flowers, Chris I; Yankaskas, Bonnie C; Zhu, Weiwei; Miglioretti, Diana L (Annals of internal medicine, 2011)
False-positive mammography results are common. Biennial screening may decrease the cumulative probability of false-positive results across many years of repeated screening but could also delay cancer diagnosis. To compare the cumulative probability of false-positive results and the stage distribution of incident breast cancer after 10 years of annual or biennial screening mammography. Prospective cohort study. 7 mammography registries in the National Cancer Institute-funded Breast Cancer Surveillance Consortium. 169,456 women who underwent first screening mammography at age 40 to 59 years between 1994 and 2006 and 4492 women with incident invasive breast cancer diagnosed between 1996 and 2006. False-positive recalls and biopsy recommendations stage distribution of incident breast cancer. False-positive recall probability was 16.3% at first and 9.6% at subsequent mammography. Probability of false-positive biopsy recommendation was 2.5% at first and 1.0% at subsequent examinations. Availability of comparison mammograms halved the odds of a false-positive recall (adjusted odds ratio, 0.50 [95% CI, 0.45 to 0.56]). When screening began at age 40 years, the cumulative probability of a woman receiving at least 1 false-positive recall after 10 years was 61.3% (CI, 59.4% to 63.1%) with annual and 41.6% (CI, 40.6% to 42.5%) with biennial screening. Cumulative probability of false-positive biopsy recommendation was 7.0% (CI, 6.1% to 7.8%) with annual and 4.8% (CI, 4.4% to 5.2%) with biennial screening. Estimates were similar when screening began at age 50 years. A non-statistically significant increase in the proportion of late-stage cancers was observed with biennial compared with annual screening (absolute increases, 3.3 percentage points [CI, -1.1 to 7.8 percentage points] for women age 40 to 49 years and 2.3 percentage points [CI, -1.0 to 5.7 percentage points] for women age 50 to 59 years) among women with incident breast cancer. Few women underwent screening over the entire 10-year period. Radiologist characteristics influence recall rates and were unavailable. Most mammograms were film rather than digital. Incident cancer was analyzed in a small sample of women who developed cancer. After 10 years of annual screening, more than half of women will receive at least 1 false-positive recall, and 7% to 9% will receive a false-positive biopsy recommendation. Biennial screening appears to reduce the cumulative probability of false-positive results after 10 years but may be associated with a small absolute increase in the probability of late-stage cancer diagnosis. National Cancer Institute.